2018
DOI: 10.1016/j.juro.2017.11.120
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation on Prostate Needle Biopsy is Associated with Lower Prostate Cancer Risk: A Meta-Analysis

Abstract: In a meta-analysis of 25 studies inflammation on prostate needle biopsy was associated with a lower prostate cancer risk. Clinically the presence of inflammation on prostate needle biopsy may lower the risk of a subsequent prostate cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
(15 reference statements)
2
27
0
Order By: Relevance
“…In addition, prostate adenocarcinoma outgrowth is frequently detected in tissue areas adjacent to chronic inflammation ( 3 , 4 ). However, other studies suggest that histologically detectable prostate inflammation associates with decreased PCa risk ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, prostate adenocarcinoma outgrowth is frequently detected in tissue areas adjacent to chronic inflammation ( 3 , 4 ). However, other studies suggest that histologically detectable prostate inflammation associates with decreased PCa risk ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 97%
“…They concluded that the presence of PCI at BNB was a negative predictor of PCa risk at re-biopsy. Furthermore, a recent meta-analysis has shown that the presence of PCI in biopsy cores is associated with a decreased risk of PCa [9]. Our previous investigations showed an inverse association between PCI and PCa.…”
Section: Pci and Pcamentioning
confidence: 50%
“…In the last few years there has been great interest in the factors that influence PCa biology. Among these, the detection of PCI at BNB has become a pivotal feature, which still remains controversial and unresolved [9].…”
Section: Pci and Pcamentioning
confidence: 99%
“…Numerous studies have been done, including mouse models, in search of inflammatory‐related prostate cancer pathways and for preventive and therapeutic purposes 32‐34 . On the other hand, several studies showed a negative association of inflammation with prostate cancer, whereby inflammation presence was associated with a lower risk or less aggressiveness of cancer, and better prognosis 35‐41 . A proposed explanation is inflammation being a host defense mechanism or protecting against prostate cancer.…”
Section: Discussionmentioning
confidence: 99%